2013
DOI: 10.1371/journal.pntd.0002176
|View full text |Cite
|
Sign up to set email alerts
|

Mode of Death on Chagas Heart Disease: Comparison with Other Etiologies. A Subanalysis of the REMADHE Prospective Trial

Abstract: BackgroundSudden death has been considered the main cause of death in patients with Chagas heart disease. Nevertheless, this information comes from a period before the introduction of drugs that changed the natural history of heart failure. We sought to study the mode of death of patients with heart failure caused by Chagas heart disease, comparing with non-Chagas cardiomyopathy.Methods and resultsWe examined the REMADHE trial and grouped patients according to etiology (Chagas vs non-Chagas) and mode of death.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(53 citation statements)
references
References 34 publications
(46 reference statements)
0
49
0
4
Order By: Relevance
“…These authors also found reduced mortality from cerebrovascular accident, other non-cardiac causes of death and longer hospital stay while comparing chagasic and non-chagasic heart diseases patients. 16 In more severe cases of Chagas disease, the only treatment capable of modifying the natural history of disease is a heart transplant. Fiorelli et al conducted a review of 107 transplant patients with a focus on disease reactivation, rejection, and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…These authors also found reduced mortality from cerebrovascular accident, other non-cardiac causes of death and longer hospital stay while comparing chagasic and non-chagasic heart diseases patients. 16 In more severe cases of Chagas disease, the only treatment capable of modifying the natural history of disease is a heart transplant. Fiorelli et al conducted a review of 107 transplant patients with a focus on disease reactivation, rejection, and mortality.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, CCC is associated with a worse prognosis and a survival rate that is one-half of the rates for cardiomyopathies of non-infl ammatory etiology (e.g., dilated cardiomyopathy and ischemic heart disease) (46) . Studies in Brazil and Venezuela have also reported that higher functional classes are associated with higher mortality rates among patients with CCC (47) (48) , with sudden death, heart failure, and ischemic stroke being the main mechanisms of death in patients with ChD (49) (50) . Our findings regarding electrocardiographic changes, such as RBBB and LAFB, are in agreement with the previous studies and are the most characteristic changes of the disease in endemic areas (51) .…”
Section: Discussionmentioning
confidence: 99%
“…45 Third, SCD affects mainly Chagas disease patients with mild to moderate CHF. 21 Fourth, activation of the sympathetic nervous system appears to occur first before that of the Renin-Aldosterone system. 49 Fifth, the probability that a Betablocker reaches the target dose following a targeted dose of ACEI is low.…”
Section: Stage Cmentioning
confidence: 99%
“…16 Autopsy studies have revealed that pulmonary embolism may be found in up to 37% of patients who died of CHF secondary to Chagas cardiomyopathy. 20 Intractable pump failure appears to be the most important cause of death in patients with Chagas disease heart failure, mainly in those with advanced forms of the disease, 21 affecting up to 43% of patients with this condition.…”
Section: Clinical Characteristics Of Chf Secondary To Chagas Cardiomymentioning
confidence: 99%